Hypnotic Responsiveness and Nonhypnotic Suggestibility: Disparate, Similar, or the Same?. Issue 1 (2nd January 2020) - Tasso, Anthony F.; Pérez, Nicole A.; Moore, Mark; Griffo, Robert; Nash, Michael R.
ABSTRACT: This study examined if participants respond to different types of suggestions, including hypnosis, uniquely or similarly. This study used 9 suggestibility measures and hypothesized a 3-factor model. It was hypothesized that hypnosis, Chevreul's pendulum, and body-sway would load on the first factor; the odor test, progressive weights, and placebo on the second factor; and conformity, persuasibility, and interrogative suggestibility would load on the third factor. The study comprised 110 college students. Factor analyses failed to result in three factors. Additional attempts at two and three-factor models were also rejected. Hypnosis had no strong relationship with the various suggestibility measures. Thus, no clearly delineated factor structure of suggestibility emerged, indicating that the domain of suggestibility seems to be neither a single attribute, trait, or group of related abilities. Implications are discussed.